1995
DOI: 10.1212/wnl.45.10.1927
|View full text |Cite
|
Sign up to set email alerts
|

Tapping the head activates the vestibular system

Abstract: We investigated the use of skull taps with a modified clinical reflex hammer as a method of vestibular activation. Using recently described EMG techniques to measure vestibulocollic reflexes in response to clicks, we were able to show analogous short-latency potentials to taps. The earliest responses were invariably absent on the side of a previous vestibular nerve section but were preserved in profound sensorineural or conductive hearing loss. We propose that the taps activated the vestibular apparatus direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(111 citation statements)
references
References 3 publications
2
107
0
2
Order By: Relevance
“…Halmagyi et al [20] reported that VEMP responses are typically absent in cases of conductive hearing loss with air-bone gap measuring ‡ 20 dB, hence the response rate of VEMPs by tone-burst method is low. In contrast, the tapping method displays higher response rate of VEMPs in patients with conductive hearing loss, indicating that the VEMP provoked by tapping with a tendon hammer on the forehead is a vibratory input rather than an auditory input [21].…”
Section: Tapping Evocation or Bone-conduction (Bc) Stimulationmentioning
confidence: 99%
“…Halmagyi et al [20] reported that VEMP responses are typically absent in cases of conductive hearing loss with air-bone gap measuring ‡ 20 dB, hence the response rate of VEMPs by tone-burst method is low. In contrast, the tapping method displays higher response rate of VEMPs in patients with conductive hearing loss, indicating that the VEMP provoked by tapping with a tendon hammer on the forehead is a vibratory input rather than an auditory input [21].…”
Section: Tapping Evocation or Bone-conduction (Bc) Stimulationmentioning
confidence: 99%
“…Vibration can stimulate vestibular afferents such as triggering the vestibulocollic reflex. Halmagyi et al (1995) induced short-latency myogenic potentials in the SCM muscle in humans by tapping the forehead. These vestibulocollic reflex potentials are absent when the vestibular nerve is sectioned, and they likely originate in a bone-conducted vibration wave stimulating the saccule.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies 2,[8][9][10][11][14][15][16]18,19,24,[28][29][30][31] , the stimuli were averaged by means of ear phones instead of the bone vibrators and the intensities were, usually, above 90 dBHL.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, stimuli above 90 dBHL are used 2,[8][9][10][11][14][15][16]18,19,24,[28][29][30][31] . However, in many studies, the threshold is surveyed by means of stimuli of different intensities (with ascending or descending techniques) until the lowest stimulus intensity capable of triggering a response is found 2,21,25,32 .…”
Section: Stimuli Averagingmentioning
confidence: 99%